"Custolytics": Internet of Things based customer analytics aiding customer engagement strategy in emerging markets – an empirical research. Issue 1 (18th September 2019) - Yerpude, Samir; Singhal, Tarun Kumar
Abstract : Purpose: The purpose of this paper is to build a customer engagement strategy for an emerging market using the Internet of Things (IoT) origin real-time data analytics for a classical retail business to customer domain. Design/methodology/approach: The study presented is twofold. First, it empirically tests a theoretical model where the impact of different parameters influencing customer engagement are validated, and its influence on the resultant parameters, i.e. brand loyalty and brand ambassador, is analyzed. Second, it emphasizes on the use of real-time IoT origin data in customer analytics to determine a customer engagement strategy. Findings: Results indicate that the four parameters, i.e., value propositions basis the buying patterns, loyalty programs, personalized communication and involving the customer in the new development process are influencing customer engagement positively, whereas the parameter loyalty program scores the maximum regression weight. IoT plays a crucial role in generating the real-time data used for generating customer analytics that proves to be vital for the longevity of the organization. Practical implications: The organizations need judicious blend of four parameters such as value proposition based on buying patterns, participation in new product development, personalized communication and loyalty program while designing the customer engagement strategy. Results drawn from the focused group interview highlight the power of IoT origin real-time data in the customer analytics further strengthening the need of customer centricity in an organization. Originality/value: Identified need of building a customer engagement strategy for an emerging market with the help of IoT data is addressed in this paper that is identified as an unexplored area and a research gap.